2016
DOI: 10.1007/s10811-016-1014-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of seaweeds as potential inhibitors of quorum sensing and bacterial growth

Abstract: Macroalgae are an important source of antimicrobial compounds. However, it is unclear if these compounds are produced by the algae themselves, by their associated bacteria, or by both. The main aim of this study was to investigate the potential of macroalgae and their associated microorganisms to inhibit bacterial quorum sensing (QS) and growth. Before extraction, half of the algal specimens were treated with 30% ethanol to remove surface associated bacteria. Canistrocarpus cervicornis extracts were able to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Another investigation on the same species, collected from the intertidal region of the Arabian Sea and Bay of Bengal, has found the methanolic extract to have anti-quorum sensing activity (Jha et al 2013 ). Other seaweed species have also been shown to produce quorum-sensing inhibitors (Carvalho et al 2017 ). Members of the genus Laurencia (Ceramiales) are also known to be a rich source of halogenated secondary metabolites (Blunt et al 2009 ) and they continue to be source of new compounds.…”
Section: Antifouling Compounds From Macroalgaementioning
confidence: 99%
“…Another investigation on the same species, collected from the intertidal region of the Arabian Sea and Bay of Bengal, has found the methanolic extract to have anti-quorum sensing activity (Jha et al 2013 ). Other seaweed species have also been shown to produce quorum-sensing inhibitors (Carvalho et al 2017 ). Members of the genus Laurencia (Ceramiales) are also known to be a rich source of halogenated secondary metabolites (Blunt et al 2009 ) and they continue to be source of new compounds.…”
Section: Antifouling Compounds From Macroalgaementioning
confidence: 99%
“…Macroalgae also show antifouling defence by different ways such as the use of chemical and physical defences (Burns et al 2003;da Gama et al 2014) or symbiotic relationships between epibionts (e.g., bacteria) (Satheesh et al 2016). Due to these chemical defence, macroalgae are one of the most important groups for natural product antifouling research (Nylund et al 2007;Hellio et al 2009;Viano et al 2009;Saha and Wahl 2013;Othmani et al 2016;Carvalho et al 2017;Salama et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several extracts and compounds derived from macroalga with the ability to inhibit quorum sensing have been reported. For example, Carvalho et al (2017) [ 231 ], reported that C. cervicornis extracts inhibited the growth of C. violaceum , due to the inhibition of the quorum sensing, since no killing effect was observed. A study conducted with P. gymnospora demonstrated that the a lpha-bisabolol obtained from this alga inhibited significantly the quorum sensing and biofilm formation of S. marcescens [ 232 ].…”
Section: Applicationsmentioning
confidence: 99%